(untitled) (Bangladesh Journal of Medical Science, 2022)
Background: Nasopharyngeal cancer (NPC) patients have high risk of cachexia. It is important to notice cachexia parameters in the beginning of their treatment in order to predict and anticipate unexpected outcomes. This study aimed to describe the profile of advanced stage NPC patient receiving first chemotherapy, especially in cachexia parameters and dietary intakes. Methods: A cross-sectional study was conducted involving advanced stage of NPC patients who would receive their first chemotherapy aged 20-70 years. Subjects with distant metastatic, acute infection, history of past chemotherapy or radiotherapy, were excluded. Parameters of cachexia being studied were inflammation markers (NLR and CRP level), anorexia and fatigue scores, body composition (fat and muscle mass) and hand grip strength (HGS), meanwhile dietary intakes were energy and protein. Frequency distribution, descriptive statistic, and Pearson correlation test were used in data analyses. Results: Forty-three subjects were participated. Average age was48.1±9.8 years old and 63% were males. NLR and CRP level were high, i.e.4.8±5.0 and 13.3±20.6 mg/dL, respectively. Anorexia and fatigue scores were 32.4±9 and 35.9±11.8, respectively, with 70% subjects were anorexic and 30% subjects experienced severe fatigue. Less than 20% were malnourished but 35% subjects had central obesity and 37% subjects classified to have very high fat mass. Most subjects had low muscle mass (77%) and classified to have weak HGS (77%). Energy and protein intakes were 26.7±8.9 kcal/kgBW/d and 1±0.4 g/kg BW/d respectively. Some variables had strong correlation (r≥0.80), i.e. BMI with visceral fat (r=0.94), fat with muscle mass (r=-0.89), energy with protein intakes (r=0.80), and moderate correlation (r=0.60–0.79) between anorexia and fatigue scores. Conclusions: Advanced stage of NPC patients receiving first chemotherapy had high inflammation status, anorexia and fatigue. Many subjects had low muscle mass and weak HGS. BMI with visceral fat, fat with muscle mass, energy with protein intake, were strongly correlated. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 302-310